2023
DOI: 10.1128/jvi.01519-22
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Regulate Acute SIV Replication, Dissemination, and Inflammation, but Do Not Impact Independent Transmission Events

Abstract: Natural killer (NK) cells as major effector cells of the innate immune system can contribute significantly to human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) control. However, a specific role for NK cells in blocking lentivirus transmission remains incompletely clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The systemic-and tissuelevel NK cell depletion achieved by the anti-IL-15 mAb administration was highly successful (Fig. 1B) with little to no adverse or off-target impacts, similar to previous reports by our group and others 24,50 and providing a clean model to evaluate the impacts on virology and pathology. The VL in our study in the pharynx peaked at 3DPI (Fig.…”
Section: Groupsupporting
confidence: 87%
See 3 more Smart Citations
“…The systemic-and tissuelevel NK cell depletion achieved by the anti-IL-15 mAb administration was highly successful (Fig. 1B) with little to no adverse or off-target impacts, similar to previous reports by our group and others 24,50 and providing a clean model to evaluate the impacts on virology and pathology. The VL in our study in the pharynx peaked at 3DPI (Fig.…”
Section: Groupsupporting
confidence: 87%
“…S2). Collectively these data indicated our NK cell depletion strategy (which has been well-defined by our group and others) 24,49,50 , was highly effective and NK cell-specific in this model. In control animals, longitudinal evaluation suggested significant NK cell mobilization in specific response to infection.…”
Section: T Cells (Supplementary Fig S1)supporting
confidence: 66%
See 2 more Smart Citations
“…Cohort studies of highly exposed seronegative (HESN) individuals have identified particular NK cell phenotypes and enhanced effector functions associated with resistance to HIV acquisition [26][27][28][29][30]. Furthermore, analysis of human samples prior to and then during acute HIV infection showed that increased NK cell activity was a correlate of future viremic control [31], and NK cell depletion in nonhuman primates (NHPs) enhanced acute viremia and inflammation [32], emphasizing the role of NK cells in control of early infection.…”
Section: Natural Killer Cell Contributions To Control Of Acute and Ch...mentioning
confidence: 99%